Analysis of Students' Ability to Understand English Narrative Texts - Lindawati; Nuzulul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study is to determine students' ability to understand narrative text at SMPN 2 Susoh. This research used a quantitative research design with the research subject of 68 eighth graders by using a written test. The descriptive analysis indicated that the majority of the students are in the poor category. The findings suggest that limited vocabulary acquisition was a critical factor contributing to their poor performance, as many students struggled to engage with the test material effectively. This lack of vocabulary affected not only their ability to complete the test but also their overall comprehension of the narrative text. Based on the result, this study highlights the urgent need for educational strategies aimed at improving vocabulary acquisition among students at SMPN 2 Susoh. By addressing this deficiency, educators can help students develop better reading comprehension skills, which will ultimately improve their academic performance in english narrative texts.